Community Empowerment Through Waste Banks to Improve Welfare - Eman Sulaiman; Hartanto Halim; Yuniva Halimatu Sadiah; Yanto Nazar Riyanto; Putri; Zufi Nurali (PT. Berkah Digital Teknologi, 2024)
The waste problem seems never-ending. If managed well and correctly waste can bring benefits, if not managed well and correctly waste can cause various negative impacts. The Berkah Mulya Waste Bank in Pegambiran Village is one of the efforts in good and correct waste management. The objectives of this service are 1) Explaining community empowerment through waste banks, 2) Explaining the supporting and inhibiting factors for the community empowerment process through waste banks, 3) Explaining welfare indicators in community empowerment at waste banks. Data collection methods include observation, interviews and documentation. The data analysis uses the reduction method, then it is briefly described and conclusions are drawn. The results show that the process of community empowerment through waste banks has gone well. Supporting factors include 1) Member involvement, 2) Facilities and infrastructure, 3) Community involvement, 4) Collaboration with other parties. Meanwhile, inhibiting factors include 1) Lack of discipline in the community, 2) Low mindset in the community, 3) Lack of interest among young people in waste management. Welfare indicators include 1) Environmental aspects, 2) Economic aspects, 3) Social aspects, 4) Educational aspects, 5) Health aspects. ABSTRAK Persoalan sampah yang seakan tidak ada habisnya. Jika dikelola dengan baik dan benar sampah dapat mendatangkan manfaat, jika tidak dikelola dengan baik dan benar sampah dapat menimbulkan berbagai dampak negatif. Bank Sampah Berkah Mulya yang berada di Kelurahan Pegambiran merupakan salah satu upaya dalam pengelolaan sampah yang baik dan benar. Tujuan dari pengabdian ini adalah 1) Menjelaskan pemberdayaan masyarakat melalui bank sampah, 2) Menjelaskan faktor pendukung dan penghambat proses pemberdayaan masyarakat melalui bank sampah, 3) Menjelaskan indikator kesejahteraan dalam pemberdayaan masyarakat di bank sampah. Metode pengumpulan data berupa observasi, wawancara dan dokumentasi. Adapun analisis data menggunakan metode reduksi kemudian diuraikan secara singkat dan penarikan kesimpulan. Hasilnya menunjukan bahwa proses pemberdayaan masyarakat melalui bank sampah sudah berjalan dengan baik. Faktor pendukung meliputi 1) Keterlibatan anggota, 2) Sarana dan prasarana, 3) Keterlibatan masyarakat, 4) Kerjasama dengan pihak lain. Sedangkan faktor penghambat melputi 1) Ketidak disiplinan masyarakat, 2) Rendahnya mindset yang dimiliki masyarakat, 3) Kurangnya minat anak muda dalam pengelolaan sampah. Indikator kesejahteraan meliputi 1) Aspek lingkungan, 2) Aspek Ekonomi, 3) Aspek sosial, 4) Aspek pendidikan, 5) Aspek kesehatan